Adaptation Of Measuring Instruments: The Adolescent Distress Eustress Scale (The Ades) - Salim Andeslan; Gardhika Rizky Sudarsono; Fadhillah Zahra Widafina; Aisyah Safira; Eva Noorlatifah; Dian Sari Utami (Publikasi Indonesia, 2024)
Adolescence is a transitional age, an individual has left a weak and dependent childhood but has not been able to reach a strong and responsible age, both for himself and society. One of the problems that arise among early adolescents is stress. The purpose of this study is to test the adolescent distress-eustress scale in adolescents spread across several islands in Indonesia. The research method carried out in this study is quantitative research. Based on the results of the analysis carried out on the 2 aspects measured in the scale adaptation, the ades meet the results of the scale adaptation test, namely the Exploratory Factor Analysis (EFA) test, the internal reliability test, and the construct validity test so that the ades scale can be used to measure distress and eustress in adolescents. It was concluded that The Adolescent Distress-Eustress Scale instrument can measure stress through two dimensions, namely distress and eustress. The results of this study show that there is evidence of good validity and reliability.